PARROT PARENTING : A BIRDTALK Book - Frischmann, Carol (Irvine, California : i-5 Publishing, 2014)
BIRDS, INCLUDING CAGE BIRDS. From the tiny parakeet to the giant hyacinth macaw, not all parrots place the same demands on their parents. Parakeets, conures, cockatiels, lories--the parrot family consists of the most popular pet birds, each offering keepers their unique characteristics and exotic beauty as well as their specific requirements. Bird expert and author, Carol Frishmann has written a must-have book for every parrot parent-to-be, an all-in-one guide that will remain indispensable in every bird home, regardless of the size, trainability, or personality of the feathered child. More than a selection guide, Parenting a Parrot offers all the information owners need to know about feeding, caring for, and training their chosen parrot. Though both good talkers, the eclectus parrot may be quieter than the cockatoo, but he's not nearly as cuddly. Parenting a Parrot tells owners what to expect from their parrots and how to get the most out of their avian companions.
Includes index.
Keywords: Parrots